Evaluation and Poverty Reduction : Proceedings from a World Bank Conference - Feinstein, Osvaldo; Picciotto, Robert (Washington, DC: World Bank, 2013)
The report covers the proceedings of the World Bank Conference on Evaluation and Development, which provided the opportunity for debate, and discussion on lessons learned from evaluations of poverty reduction programs, to partnerships, and participation in evaluation. It presents the addresses of the plenary sessions, papers, and excerpts, on the Conference topics, which included the role of targeted poverty reduction policies, and programs, the design of social funds, safety nets, and ways to include civil society, and private participation towards effective development. Evaluation methodologies figured prominently in the conference discussions, focusing on measuring development impact, with special emphasis on factoring in externalities, and in evaluation design. The lessons learned, question poverty reduction strategies, describing instead the success in making development interventions context-specific, in taking a holistic view, and in broadening the poverty concept. Institutional change is addressed in the context of social capital, stressing its impact as a major challenge for future poverty alleviation efforts. To summarize, the need to better reconcile the different expectations, particularly that of the poor, is emphasized, as well as the need for decisive strategic evaluation.